A Patient-Centered Evaluation of Meaningful Change on the 32-Item Motor Function Measure in Spinal Muscular Atrophy Using Qualitative and Quantitative Data - Duong, Tina; Staunton, Hannah; Braid, Jessica; Barriere, Aurelie; Trzaskoma, Ben; Gao, Ling; Willgoss, Tom; Cruz, Rosangel; Gusset, Nicole; Gorni, Ksenija; Randhawa, Sharan; Yang, Lida; et al. (Frontiers in Neurology, 2022)
The 32-item Motor Function Measure (MFM32) is an assessment of motor function used to evaluate fine and gross motor ability in patients with neuromuscular disorders, including spinal muscular atrophy (SMA). Reliability and validity of the MFM32 have been documented in individuals with SMA. Through semi-structured qualitative interviews (N = 40) and an online survey in eight countries (N = 217) with individuals with Types 2 and 3 SMA aged 2–59 years old and caregivers, the meaning of changes on a patient-friendly version of the MFM32 was explored. In an independent analysis of clinical trial data, anchor- and distribution-based analyses were conducted in a sample of individuals with Type 2 and non-ambulant Type 3 SMA to estimate patient-centered quantitative MFM32 meaningful change thresholds. The results from this study demonstrate that, based on patient and caregiver insights, maintaining functional ability as assessed by a patient-friendly version of the MFM32 is an important outcome. Quantitative analyses using multiple anchors (median age range of 5–8 years old across anchor groups) indicated that an 3-point improvement in MFM32 total score represents meaningful change at the individual patient level. Overall, the qualitative and quantitative findings from this study support the importance of examining a range of meaningful change thresholds on the MFM32 including ≥0 points change reflecting stabilization or improvement and ≥3 points change reflecting a higher threshold of improvement. Future research is needed to explore quantitative differences in meaningful change on the MFM32 based on age and functional subgroups.